Representasi Mental Disorders Lagu “Amygdala” Suga BTS Melalui Analisis Semiotika Charles Sanders Peirce - Wahyuni, Sri; Pudrianisa, Sheila Lestari Giza (AGUNA: Jurnal Ilmu Komunikasi, 2024)
Mental health disorders ones of the diseases that cannot be seen physically because someone will be attacked inwardly and even change drastically. In many young people of generation Z affected by mental health, thus making one of the BTS personnel, Suga, express it in the form of a song entitled